Syntax Errors in English Writing - Reski, Andi Nur (Educia Journal, 2023)
This paper discusses syntactic errors in English writing which are caused by inaccuracy in rules, principles, and processes that govern the structure of sentences. The aims of this paper are to know the syntactic errors in English writing. The method in conducting this paper, the author uses a descriptive method to analyse data. It is used to describe syntactic errors made by English students writing.